(untitled) (Bangladesh Journal of Botany, 2010)
Lamprothamnium papulosum (Wall.) J. Groves has been reported and described for the first time from Bangladesh. Key words: Lamprothamnium papulosum; Charophyta; Bangladesh DOI: 10.3329/bjb.v39i1.5535 Bangladesh J. Bot. 39(1): 111-114, 2010 (June)